2018
DOI: 10.5114/pjp.2018.75340
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphisms of XRCC3 gene in hepatocellular carcinoma – relationship with clinicopathological features

Abstract: Recent studies support the involvement of XRCC3 gene polymorphisms in carcinogenesis. Our study focuses on the identification of polymorphic variants of XRCC3 in hepatocellular carcinoma (HCC) and an analysis of the relationship between these polymorphic variants and clinicopathological (including the genotype specific risk) and survival characteristics. Fifty cases of HCC were genotyped using molecular biology techniques for Thr241Met, rs861539 (c.722C>T) and 5'-UTR, rs1799796 (c.562-14A>G) polymorphisms. Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Similar to XRCC1 and XRCC2, XRCC3 has been researched widely in the correlation between gene polymorphisms and the risk of cancer. Several studies have revealed multiple gene mutations, including rs861539 C > T, rs1799796 A > G, C241T, which are significantly associated with enhanced risk of HCC [38,39]. Besides, XRCC3 overexpression has been found to be associated with clinical factors in breast cancer [40].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to XRCC1 and XRCC2, XRCC3 has been researched widely in the correlation between gene polymorphisms and the risk of cancer. Several studies have revealed multiple gene mutations, including rs861539 C > T, rs1799796 A > G, C241T, which are significantly associated with enhanced risk of HCC [38,39]. Besides, XRCC3 overexpression has been found to be associated with clinical factors in breast cancer [40].…”
Section: Discussionmentioning
confidence: 99%
“…XRCC3 (X-ray complementing defective repair in Chinese hamster cells) encodes a Rad51 paralog which is involved in double-strand break repair and could be involved in error-free by pass of AFB1associated DNA lesions. The XRCC3 rs861539 allele (codon Thr241Met polymorphism) is a risk factor for HCC, and the risk is aggravated if individuals are exposed to AFB1 [62][63][64]. Other alleles that have been associated with higher risk for HCC include those participating in the base excision repair (BER) and NER pathways, such as XRCC1 rs25487 polymorphism (codon Arg399Gln polymorphism) [65,66] and XPD rs25487 polymorphism, respectively [67].…”
Section: Gene Polymorphisms Associated With Afb1-associated Liver Cancermentioning
confidence: 99%
“…It has not yet been determined whether mammalian cells defective in homologous recombination exhibit more AFB1associated mutations. Nonetheless, it is interesting that polymorphisms of XRCC3 [62][63][64], which functions in homologous recombination, are a risk factor for HCC.…”
Section: Template-switch Mechanisms As An Alternative Mechanism For Tmentioning
confidence: 99%
“…A large number of genetic alterations and molecular factors have been shown to associate with the progression of HCC, and they have potential prognostic significance [6,14]. Understanding the molecular pathways in liver carcinogenesis and identification of molecules as targets for therapeutic intervention give hope for better prognosis of patients with HCC [11].…”
Section: Molecular Markersmentioning
confidence: 99%
“…Besides the fundamental role β-catenin has regulating the E-cadherin-catenin cell adhesion complex, β-catenin also acts as a transcriptional activator of the Wnt signalling pathway and regulates transcription of target genes responsible for cell proliferation and differentiation [19][20][21]. Many authors have studied the genetic alteration of E-cadherin and β-catenin, their related pathways, and expression of E-cadherin and β-catenin molecules in various cancers including HCC [5,14,22,23]. Reduced E-cadherin expression is associated with the progression of HCC, poor prognosis, poor differentiation, metastasis, and TNM stage [17,21,24,25,26].…”
Section: Molecular Markersmentioning
confidence: 99%